2016
DOI: 10.1002/pen.24441
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and Component Properties of Polyamide 12 at Processing‐Relevant Cooling Conditions

Abstract: For semicrystalline thermoplastics, the temperature-time behavior during cooling of the melt can significantly affect the formation of crystalline structures (e.g., spherulite sizes, the degree of crystallization, crystal modifications, etc.) and hence, the resulting global component properties. In this paper, the crystallization of polyamide 12 at different cooling rates as well as process-based temperature-time profiles during cooling were investigated analytically with fast scanning calorimetry. Furthermore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 20 publications
2
33
0
Order By: Relevance
“…Furthermore, a material with relatively high crystallization kinetic has been investigated for comparison reasons since here, it is estimated that there is no significant influence of isothermal holding time, also compare Refs. . For this purpose, POM‐C (Hostaform C9021), supplied by Ticona, was used.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, a material with relatively high crystallization kinetic has been investigated for comparison reasons since here, it is estimated that there is no significant influence of isothermal holding time, also compare Refs. . For this purpose, POM‐C (Hostaform C9021), supplied by Ticona, was used.…”
Section: Methodsmentioning
confidence: 99%
“…In Refs. it could be shown that an increase of the mold temperature leads to a decrease of the oriented skin near layer thickness of the component and also an increase of the measured degree of crystallization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An analysis of publications on the production of flat polymeric films [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] showed that majority of them are devoted to numerical and experimental modeling of separate stages of their production process. The focus on the process of preparation of polymer melt in the extruder [7][8][9][10], as well as the process of orientation of semi-finished film on the section from the extrusion head to the cooling drum [11][12][13][14][15][16].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Paper [18] contains results of research in cooling a film from polyamide 12 on the drum, in this case, temperature of the drum was accepted as constant, which is justified for a thin film with thickness of 80 μm, but is unacceptable for thick films.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%